1964
DOI: 10.1128/aem.12.2.127-131.1964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Recovery of Escherichia coli from Frozen Foods and Nutmeats by Confirmatory Incubation in EC Medium at 44.5 and 45.5 C

Abstract: FISHBEIN, MORRIS (Food and Drug Administration, Washington, D.C.), AND BERNARD F. SURKIEWICZ. Comparison of the recovery of Escherichia coli from frozen foods and nutmeats by confirmatory incubation in EC medium at 44.5 and 45.5 C. Appl. Microbiol. 12:127-131. 1964.-The productivity of confirmatory EC broth for the isolation of fecal Escherichia coli was determined at 44.5 and 45.5 C. A variety of frozen precooked foods and an assortment of nutmeats were examined after primary incubation in Lauryl Sulfate Tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1967
1967
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Considerable emphasis is placed on the production of gas from lactose at elevated incubation temperature to determine fecal origin of F. c(oli, or E. c(oli biotype 1 (13). In North America, incubation temperatures of 44.5 to 45.5°C are used to reduce the incidence of false-positive results and because gas production from lactose has been shown to be more specific for fecal E. coli at these temperatures (12). In Europe, it is believed that specificity for E. coli as an indicator organism is obtained with an elevated incubation temperature of 44°C for gas production from lactose and indole production (10).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable emphasis is placed on the production of gas from lactose at elevated incubation temperature to determine fecal origin of F. c(oli, or E. c(oli biotype 1 (13). In North America, incubation temperatures of 44.5 to 45.5°C are used to reduce the incidence of false-positive results and because gas production from lactose has been shown to be more specific for fecal E. coli at these temperatures (12). In Europe, it is believed that specificity for E. coli as an indicator organism is obtained with an elevated incubation temperature of 44°C for gas production from lactose and indole production (10).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show the improvement effected by the 1 C reduction in EC broth incubation temperature-both a 19% increase in verification for the rapid method, with an improved log variance, and a substantial increase in the verified standard MPN count. Fishbein (9,10), working with pure cultures of E. coli and Aerobacter strains and also with frozen foods and nutmeats, concluded that 44.5 C was too low a temperature for EC broth incubation. Many Aerobacter strains and a significant number of non-E. coli strains isolated from the food products studied were verified as positive.…”
Section: 2mentioning
confidence: 99%
“…d Fishbein and Surkiewicz (3). e The number of positive tubes in the E C (45.5 C) confirmatory test.…”
Section: Lst-35c(w Ec-35c(x) Lst-44c( Ec-44c(z)mentioning
confidence: 99%